Short Communication: Notes on a new distribution record of the Critically Endangered Sunda Pangolin (Manis javanica) in Sabah, Malaysian Borneo - Jephte Sompud; Nurhidayah Sahar; Carmen Adros; Evelyn Richard; Cynthia Boon Sompud (Society for Indonesian Biodivers, 2023)
Many language experts and researcher emphasised the crucial awareness and intervention to accentuate listening comprehension. However, listening skill is the least prominent and seldom tackled compared to other language skills. Listening is the key to an effective communication in university and in real life. It is used widely during tertiary education and associated to the overall academic achievement. Listening skill was not developed enough to effectively process the input from various resources across disciplines. Students also often perceive that listening is an innate skill and will be improved naturally. But listening skill can be very complex where students need to direct focus, derive meaning, and differentiate the sound. Therefore, they need to have a clear understanding of the processes involved in listening comprehension. Additionally, they need to integrate strategies that can be used to enhance comprehension. Having self-efficacy beliefs and employing the appropriate listening strategies can improve focus and promote listening comprehension. This study probe on the relationship between listening self-efficacy and metacognitive awareness of listening strategies (MALS). Two instruments were utilised in this study which are English Listening Self-Efficacy Questionnaire (ELSEQ) and Metacognitive Awareness of Listening Strategies Questionnaire (MALQ). Students showed moderate level of listening self-efficacy in this study. Next, students partly agreed with the metacognitive awareness of listening strategies, and problem solving has the highest average score followed by directed attention. Equally important, there was a positive correlation between the learner’s self-efficacy beliefs and the average score of their MALS. This study is hoped to shed the light on listening skill empirically so that students can progress their listening process during their degree study